Clinical Practice Guideline: Evaluation of the Neck Mass in Adults. (10th September 2017) - Pynnonen, Melissa A.; Gillespie, M. Boyd; Roman, Benjamin; Rosenfeld, Richard M.; Tunkel, David E.; Bontempo, Laura; Brook, Itzhak; Chick, Davoren Ann; Colandrea, Maria; Finestone, Sandra A.; Fowler, Jason C.; Griffith, Christopher C.; et al.
Abstract : Objective: Neck masses are common in adults, but often the underlying etiology is not easily identifiable. While infections cause most of the neck masses in children, most persistent neck masses in adults are neoplasms. Malignant neoplasms far exceed any other etiology of adult neck mass. Importantly, an asymptomatic neck mass may be the initial or only clinically apparent manifestation of head and neck cancer, such as squamous cell carcinoma (HNSCC), lymphoma, thyroid, or salivary gland cancer. Evidence suggests that a neck mass in the adult patient should be considered malignant until proven otherwise. Timely diagnosis of a neck mass due to metastatic HNSCC is paramount because delayed diagnosis directly affects tumor stage and worsens prognosis. Unfortunately, despite substantial advances in testing modalities over the last few decades, diagnostic delays are common. Currently, there is only 1 evidence‐based clinical practice guideline to assist clinicians in evaluating an adult with a neck mass. Additionally, much of the available information is fragmented, disorganized, or focused on specific etiologies. In addition, although there is literature related to the diagnostic accuracy of individual tests, there is little guidance about rational sequencing of tests in the course of clinical care. This guideline strives to bring a coherent, evidence‐based, multidisciplinary perspective to the evaluation of the neck mass with the intention to facilitate prompt diagnosis and enhance patient outcomes. Purpose: The primary purpose of this guideline is to promote the efficient, effective, and accurate diagnostic workup of neck masses to ensure that adults with potentially malignant disease receive prompt diagnosis and intervention to optimize outcomes. Specific goals include reducing delays in diagnosis of HNSCC; promoting appropriate testing, including imaging, pathologic evaluation, and empiric medical therapies; reducing inappropriate testing; and promoting appropriate physical examination when cancer is suspected. The target patient for this guideline is anyone ≥18 years old with a neck mass. The target clinician for this guideline is anyone who may be the first clinician whom a patient with a neck mass encounters. This includes clinicians in primary care, dentistry, and emergency medicine, as well as pathologists and radiologists who have a role in diagnosing neck masses. This guideline does not apply to children. This guideline addresses the initial broad differential diagnosis of a neck mass in an adult. However, the intention is only to assist the clinician with a basic understanding of the broad array of possible entities. The intention is not to direct management of a neck mass known to originate from thyroid, salivary gland, mandibular, or dental pathology as management recommendations for these etiologies already exist. This guideline also does not address the subsequent management of specific pathologic entities, as treatment recommendations for benign and malignant neck masses can be found elsewhere. Instead, this guideline is restricted to addressing the appropriate work‐up of an adult patient with a neck mass that may be malignant in order to expedite diagnosis and referral to a head and neck cancer specialist. The Guideline Development Group sought to craft a set of actionable statements relevant to diagnostic decisions made by a clinician in the workup of an adult patient with a neck mass. Furthermore, where possible, the Guideline Development Group incorporated evidence to promote high‐quality and cost‐effective care. Action Statements: The development group made a strong recommendation that clinicians should order a neck computed tomography (or magnetic resonance imaging) with contrast for patients with a neck mass deemed at increased risk for malignancy. The development group made the following recommendations : (1) Clinicians should identify patients with a neck mass who are at increased risk for malignancy because the patient lacks a history of infectious etiology and the mass has been present for ≥2 weeks without significant fluctuation or the mass is of uncertain duration. (2) Clinicians should identify patients with a neck mass who are at increased risk for malignancy based on ≥1 of these physical examination characteristics: fixation to adjacent tissues, firm consistency, size >1.5 cm, or ulceration of overlying skin. (3) Clinicians should conduct an initial history and physical examination for patients with a neck mass to identify those with other suspicious findings that represent an increased risk for malignancy. (4) For patients with a neck mass who are not at increased risk for malignancy, clinicians or their designees should advise patients of criteria that would trigger the need for additional evaluation. Clinicians or their designees should also document a plan for follow‐up to assess resolution or final diagnosis. (5) For patients with a neck mass who are deemed at increased risk for malignancy, clinicians or their designees should explain to the patient the significance of being at increased risk and explain any recommended diagnostic tests. (6) Clinicians should perform, or refer the patient to a clinician who can perform, a targeted physical examination (including visualizing the mucosa of the larynx, base of tongue, and pharynx) for patients with a neck mass deemed at increased risk for malignancy. (7) Clinicians should perform fine‐needle aspiration (FNA) instead of open biopsy, or refer the patient to someone who can perform FNA, for patients with a neck mass deemed at increased risk for malignancy when the diagnosis of the neck mass remains uncertain. (8) For patients with a neck mass deemed at increased risk for malignancy, clinicians should continue evaluation of patients with a cystic neck mass, as determined by FNA or imaging studies, until a diagnosis is obtained and should not assume that the mass is benign. (9) Clinicians should obtain additional ancillary tests based on the patient's history and physical examination when a patient with a neck mass is deemed at increased risk for malignancy who does not have a diagnosis after FNA and imaging. (10) Clinicians should recommend evaluation of the upper aerodigestive tract under anesthesia, before open biopsy, for patients with a neck mass deemed at increased risk for malignancy and without a diagnosis or primary site identified with FNA, imaging, and/or ancillary tests. The development group recommended against clinicians routinely prescribing antibiotic therapy for patients with a neck mass unless there are signs and symptoms of bacterial infection.